Amorphous nickel boride membrane coated PdCuCo dendrites as high-efficiency catalyst for oxygen reduction and methanol oxidation reaction. (June 2019) - Li, Tingting; Li, Shuo; Zuo, Yunpeng; Zhu, Guilin; Han, Heyou
Abstract: Extensive efforts have been devoted to improve electrocatalytic activity of the catalysts in the fuel cells, however, it's still a big challenge to obtain the catalysts with low-cost and high-efficiency. Here we report the branched PdCuCo catalyst coated by amorphous nickel boride membrane displays an effective activity toward oxygen reduction reaction (ORR) and methanol oxidation reaction (MOR). The coating membrane serves as an electron acceptor to tune the surface electronic structure of the catalyst. And the interactional effect of the composite catalysts exhibit a normal distribution trend of mass activity (MA) and specific activity (SA) for the ORR and MOR. The SA of the composite catalysts effectively improves 3.3 times for ORR and 4.1 times for MOR than PdCuCo. Moreover, the proposed cost-effective catalyst can inspire novel design perspective about the focus attention of catalytic activity. Graphical abstract: Amorphous Ni-B membrane coated branched PdCuCo electrocatalysts exhibit improved catalytic activity for the oxygen reduction and methanol oxidation reaction due to the effective electronic tuning effects between branched PdCuCo alloy and amorphous NiB membrane. The thickness of the coating can induce a normal distribution trend of mass activity and specific activity.Image 1 Highlights: Amorphous Ni-B membrane coated branched PdCuCo electrocatalysts are fabricated. The Ni-B membrane serves as an electron acceptor to tune the surface electronic structure of the electrocatalysts. The interface interactional effect of the composite catalysts can induce improved electrocatalytic activity for the oxygen reduction and methanol oxidation reaction.